The effect of several herbs on the population of sitophilus oryzae / Syakirah Nurizzati Mohamad Hood - Mohamad Hood, Syakirah Nurizzati (Faculty of Applied Sciences, 2014)
The purpose of this study was to investigate the effect of selected fresh local herbs on alive Sitophilus oryzae, which also known as rice weevil. This study was conducted by using 9 samples of fresh herbs obtained from local wet markets and supermarket in Kuala Pilah, Negeri Sembilan. Sitophilus oryzae was obtained from infested rice storage, and reared in laboratory. The main observation of this study is to record the mortality rate of Sitophilus oryzae, provided with five days of treatment period. The samples tested are Pandanus amarylifolius (Pandan leaves), Cymbopogon citrates (lemongrass), Etlingera elatior (torch ginger), Piper betel (betel leaves), Citrus hystrix (kaffir lime) leaves, Murraya koenigii (curry) leaves, Zingiber officinale (ginger), Capsicum frutescens (bird eye chili) and Curcuma longa (turmeric). The most effective herbs which can kill the most number of Sitophilus oryzae individuals is Capsicum frutescens while the least effective herb is Piper betel.